Analysis of Burnout Syndrome Levels Among Nurses at Baubau Regional General Hospital - Mitha Rahmilah; Meliana Handayani; Wa Ode Maghfira Nurul Insani (Science Tech Group, 2026)
Burnout syndrome is a condition characterized by physical, emotional, and mental exhaustion resulting from prolonged work-related stress, which may negatively affect the quality of nursing care services. Nurses, as healthcare professionals with high work intensity, are particularly vulnerable to burnout due to complex and continuous job demands. This study aimed to describe the prevalence of burnout syndrome among nurses at Baubau Regional General Hospital and to support occupational mental health promotion in line with Sustainable Development Goals (SDGs) 3.4, 3.c, and 8.8. A quantitative study with a cross-sectional descriptive design was conducted involving 146 nurses selected through simple random sampling. Data were collected using the 22-item Maslach Burnout Inventory-Human Services Survey (MBI-HSS), which measures three dimensions of burnout: emotional exhaustion, depersonalization, and personal accomplishment. The results showed that most respondents had low levels of emotional exhaustion (93.8%) and depersonalization (64.4%), while the majority demonstrated high levels of personal accomplishment (63.0%). These findings indicate that most nurses at Baubau Regional General Hospital had not experienced severe burnout syndrome and generally maintained a relatively good psychological work condition. Nevertheless, several respondents demonstrated moderate to high levels of depersonalization and emotional exhaustion, which require attention. Therefore, burnout prevention efforts are needed through effective workload management, psychosocial support, and strengthening occupational health programs for nurses.